2009
DOI: 10.3340/jkns.2009.46.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Remote Cerebellar Hemorrhage Complicated after Supratentorial Surgery: Retrospective Study with Review of Articles

Abstract: RCH is a rare complication after supratentorial surgery, and the exact etiology still remains uncertain. Hypertension and perioperative loss of CSF seem positively correlated with RCH, but no single risk factor is totally responsible. Patients with RCH should be closely observed to improve their prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 28 publications
0
55
0
3
Order By: Relevance
“…However, the rate of RCH following supratentorial craniotomy is lower, ranging from 7.8% to 14.8%. 4,16 Many studies have used management approaches similar to those used for spontaneous cerebellar hematoma, even though the natural history of the two entities is different. 14 The literature on the management of RCH is limited to retrospective clinical studies of small cohorts, mainly adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of RCH following supratentorial craniotomy is lower, ranging from 7.8% to 14.8%. 4,16 Many studies have used management approaches similar to those used for spontaneous cerebellar hematoma, even though the natural history of the two entities is different. 14 The literature on the management of RCH is limited to retrospective clinical studies of small cohorts, mainly adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…RCH after a supratentorial craniotomy can be treated conservatively or decompressed using a ventricular drain or craniectomy with good clinical outcomes. 4,10,12,16,19 With excessive loss of CSF and RCH observed on CT imaging, drains should be discontinued to prevent exacerbation of the RCH. 4 Other authors have recommended against the use of suction drainage 11,21 and intraoperative mannitol for procedures at higher risk of RCH (hemorrhage severity and patient age).…”
Section: Discussionmentioning
confidence: 99%
“…Even though Freidman JA et al, reported that the use of ASA (Acetylsalicylic Acid) increased the risk of RCH, they pointed out that there were no differences between control and RCH patients' coagulation parameters [4]. Arterial hypertension was also considered as a predisposing [3,[9][10][11]. In a retrospective study, it has been postulated that intraoperative hypertension plays a particular role in the development of postoperative RCH [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have attributed the sagging of the cerebellum following spinal surgery to CSF discharge and to injury that occurred during the surgery [1] [5] [7]. Park et al suggested that it mostly originated from the venous system, particularly the superior vermian vein, and concluded that RCHs were the result of excessive CSF discharge [17].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, it is caused by bilateral injury of the superior cerebellar vein. RCHs mostly occur in the tentorium wall of cerebellar parenchyma and in the dentate nucleus region [17]. On CT, they show up as parallel flat hyperdense areas known as the zebra sign [7] [8].…”
Section: Discussionmentioning
confidence: 99%